ANALISIS STRATEGI PERIKLANAN DARING DALAM MEMPROMOSIKAN DESSERT BOX BITTERSWEET BY NAJLA MELALUI MEDIA SOSIAL INSTAGRAM - Raihan (2022)
Bittersweet by Najla has promoted on social media using Instagram as its main promotional media. The insights generated from the use of these promotional media show relatively good numbers from its competitors. However, the rise of competitors offering similar products poses a threat to Bittersweet by Najla's sales. This raises the question, how big is the level of public awareness of Bittersweet by Najla? What is the potential for the downward trend of Biitersweet by Najla? Then, how is the online advertising strategy built to overcome these problems? This will be discussed in this research.